2022
DOI: 10.1210/endocr/bqac075
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Crosstalk Between Thyroid and Breast Cancer

Abstract: Differentiated thyroid cancer and breast cancer account for a significant portion of endocrine-related malignancies and predominately affect women. As hormonally responsive tissues, the breast and thyroid share endocrine signaling. Breast cells are responsive to thyroid hormone signaling and are affected by altered thyroid hormone levels. Thyroid cells are responsive to sex hormones, particularly estrogen, and undergo pro-tumorigenic processes upon estrogen stimulation. Thyroid and sex hormones also display si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 263 publications
0
10
0
Order By: Relevance
“…The role of estrogen in breast cancer (BC) has been confirmed, and more and more studies have recently confirmed the importance of estrogen in the development of TC [8][9][10]. Studying the molecular mechanism of estrogen in TC, is of great significance for clarifying the sex difference in TC pathogenesis, precision treatment and prognosis of TC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The role of estrogen in breast cancer (BC) has been confirmed, and more and more studies have recently confirmed the importance of estrogen in the development of TC [8][9][10]. Studying the molecular mechanism of estrogen in TC, is of great significance for clarifying the sex difference in TC pathogenesis, precision treatment and prognosis of TC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several mechanistic studies have confirmed the role of oestrogen and its receptors in the promotion of TC 19,20 . Oestrogen and its receptors have previously been extensively studied in breast cancer, but this endocrine fluctuation may also be associated with the thyroid, and studies have now shown a correlation between breast cancer and TC 21,22 …”
Section: Discussionmentioning
confidence: 93%
“…19,20 Oestrogen and its receptors have previously been extensively studied in breast cancer, but this endocrine fluctuation may also be associated with the thyroid, and studies have now shown a correlation between breast cancer and TC. 21,22 Sex differences are a potential influencing factor in prognosis, oestrogen levels in women begin to decline significantly. Therefore, we set the cut-off age of menopause as 50 years in this study, 23,24 which is consistent with the grouping of many studies on perimenopause.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that breast cells are responsive to thyroid hormone signaling and are affected by altered thyroid hormone levels. 16 However, further studies are needed to confirm the relevant mechanism.…”
Section: Discussionmentioning
confidence: 99%